Analysis of problems, consequences and solutions for BIM application in reconstruction projects - Migilinskas, Darius; Pavlovskis, Miroslavas; Urba, Irina; Zigmund, Viačeslav (Journal of Civil Engineering and Management, 2017)
The main aim of analysis presented in this paper is based on the complex evaluation of Building Information Modelling (BIM) application and decision support in reconstruction projects. The reconstruction projects face the high level uncertainty during implementation mostly due inappropriate information management, insufficient quality control and low competence of participants. The application of advanced Computer-Aided tools such as BIM uses both with advanced Information and Communication Technologies (ICT) can be the way to solve the problems of reconstruction projects. The fourteen reconstruction projects have been analysed and the list of thirteen main problems has been identified. The pair wise judgment of problems has been made based on in the expert survey using the Analytic Hierarchy Process (AHP) method. The occurrence, influence to project and significance of the problems have been calculated and were prioritised according to the importance and consequences. After the complex analysis of problems, it is suggested to use combined list of solutions of the BIM tool application in reconstruction projects to support decision making process.